- #1

sponsoredwalk

- 532

- 5

[tex]f(z) = \sqrt{z} + \sqrt{1 - z}[/tex]

[tex]f(z) = \sqrt{z} + \sqrt{z - 1}[/tex]

[tex]f(z) = \sqrt{z} + \sqrt{z(z - 1)}[/tex]

[tex]f(z) = log(z - 1) + \sqrt{z}[/tex]

In other words: how does one understand the algebra of branch cuts and branch points, i.e. the branch cut of a sum is the sum of the branch cuts or whatever the rule is, in general? It really would be fantastic if someone could help me out with this, I have no idea myself & can't find it discussed anywhere.